Evaluation of serum homocysteine level and its relation with carotid intima-media thickness in patients of chronic kidney disease - Jain, Deepak; Aggarwal, Hari Krishan; Goyal, Shivraj; Sen, Jyotsana; Seth, Shashi (Medical Studies/Studia Medyczne, 2017)
Introduction: Patients with chronic kidney disease (CKD) are at high risk for the development of cardiovascular disease (CVD). The intima-media thickness (IMT) is the best-studied sonographic marker for early atherosclerotic vascular wall lesions. Homocysteine is an important non-traditional risk factor for CVD in CKD patients. Aim of the research : To explore the relationship between elevated serum homocysteine level and its relationship with carotid intima-media thickness in patients with CKD. Material and methods : The study was undertaken in 60 adult patients with chronic renal failure. The patients were divided into three groups: group I had subjects with CKD (stage 3); group II had subjects with CKD (stage 4) on conservative therapy; and group III had subjects with CKD (stage 5) on regular haemodialysis at least 3–4 times per week. Carotid sonography was done in all patients at the time of inclusion in the study. The patients in all the groups were then followed for 3 months and the relevant investigations were carried out, initially at the time of presentation, and then at 3 months in group III patients. The patients were monitored for various renal parameters along with serum homocysteine. Results: The value of carotid intima-media thickness (CA-IMT) was increased in groups II and III as compared to group I. Patients in group III had higher levels of serum homocysteine as compared to patients in groups I and group II. The comparison of homocysteine levels between three groups was also highly statistically significant. No correlation was observed between serum homocysteine levels and carotid artery IMT in all the three groups. Conclusions : The present observations show that baseline serum homocysteine levels and carotid artery IMT levels were elevated at baseline in all the three groups, with progressive increase in their values with decline in renal function.